Implementation of CNIL’s Basic Logging Measures in Indonesia: A Juridical Study on Personal Data Protection - Putra, Tegar Islami; Fibrianti, Nurul; Fakhis, Adinda Zeranica Putri (The Indonesian Journal of International Clinical Legal Education, 2025)
One of the efforts to realize preventive efforts to prevent all risks of personal data protection is to establish basic precaution logging as a personal data protection strategy that will serve as a guide for parties involved in personal data protection efforts. Indonesia, which has not formulated such a strategy, can make the provisions in France as a reference. The urgency of this research is that there is a mandate in Article 59 letter a of the Personal Data Protection Law in Indonesia for the Institution to formulate and determine policies and strategies for Personal Data Protection as a guide. This research employs the Library Research method, also known as Legal Research, which focuses on analyzing primary and secondary legal materials based on literature. The results show that France already has an institution called CNIL which formulates basic precautions in logging operations to guide personal data protection strategies. As a result, there are 8 basic precautions in logging operations, which are to provide a logging system that can implement and learn by Indonesia, that are: keep these logs for a rolling period of between six months and one year; perform, for application logs, a record of the creation, consultation, sharing, modification, and deletion; inform users; protect the logging equipment and the logged information; ensure the proper functioning of the logging system; ensure that processors are contractually obliged; and actively analyze, in real time or in the short term.